2013
DOI: 10.1007/s11999-013-3025-4
|View full text |Cite
|
Sign up to set email alerts
|

Is Lateral Pin Fixation for Displaced Supracondylar Fractures of the Humerus Better Than Crossed Pins in Children?

Abstract: Background Closed reduction and percutaneous pin fixation is considered standard management for displaced supracondylar fractures of the humerus in children. However, controversy exists regarding whether to use an isolated lateral entry or a crossed medial and lateral pinning technique. Questions/purposes We performed a meta-analysis of randomized controlled trials (RCTs) to compare (1) the risk of iatrogenic ulnar nerve injury caused by pin fixation, (2) the quality of fracture reduction in terms of the radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 52 publications
3
47
2
Order By: Relevance
“…For this reason, this configuration has been employed for several years and guaranteed higher stability. However, Slobogean et al [12] reported that the cross-wired configuration leads to an increased risk of iatrogenic damage to the ulnar nerve versus a lateral K-wire [25].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, this configuration has been employed for several years and guaranteed higher stability. However, Slobogean et al [12] reported that the cross-wired configuration leads to an increased risk of iatrogenic damage to the ulnar nerve versus a lateral K-wire [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nerve injury occurred at a weighted event rate of 4.1% where crossed pins were used, whereas the use of lateralonly pinning caused neurapraxia at a weighted event rate of 3.4% [44]. Similarly, a recent meta-analysis of randomized controlled trials by Zhao et al [51] supported the assertion that iatrogenic ulnar nerve injury was higher with the crossed pinning technique than with the lateral entry technique. In a systematic review by Slobogean et al [50], the number needed to harm for ulnar nerve injury was reported to be 28 in crossed pinning.…”
Section: Surgical Techniquesmentioning
confidence: 90%
“…[10,19] In a meta-analysis of randomized controlled trials, crossedpinning fixation was determined to carry greater risk of iatrogenic ulnar nerve injury than lateral pinning, and the later technique was recommended. [20] In a single retrospective cohort study that included 65 patients (29 Gartland type III and 36 Gartland type II fractures), authors reported 1 iatrogenic ulnar nerve injury and recommended crossed-pin fixation with mini-open technique as a safe and reliable method. [4] The present is the first study to compare medial mini-open crossed-pinning and percutaneous crossed-pinning techniques.…”
Section: Introductionmentioning
confidence: 99%